Achilles Tension Mitigates Fibular Malalignment Measured in Cadaveric Studies of Syndesmotic Clamping. (April 2019) - Goetz, Jessica E.; Szabo, Nicole; Rudert, M. James; Karam, Matthew D.; Phisitkul, Phinit
Background: Fibular malreduction is becoming a commonly recognized complication of surgical repair of the syndesmosis when a reduction clamp is used. The goal of this work was to determine the interdependent effects of transsyndesmotic reduction clamp position and applied compression force on fibular alignment in a realistic cadaveric preparation of complete syndesmotic injury. Methods: Six through-the-knee cadaveric specimens were CT scanned intact, with the distal syndesmosis fully destabilized, and with 53, 102, and 160 N clamping forces each applied along an anteriorly, centrally, and posteriorly directed transsyndesmotic axis. Testing was repeated incorporating 178 N of Achilles tendon tension using all 3 clamping forces applied along the centrally directed axis. Fibular reduction was automatically quantified from CT scan–generated bony surfaces as rotation of the fibula around the tibia, rotation of the fibula within the incisura, medial/lateral fibular displacement, and anterior/posterior fibular displacement. Results: Transsyndesmotic clamping along the anteriorly directed axis resulted in the best reduction quality by all 4 quantified measures. Along the centrally and posteriorly directed axes, progressively greater forces caused significantly greater sagittal plane fibular malreduction. Addition of Achilles tension reduced the magnitude of fibular malreduction and overcompression. Conclusion: Placing the medial tine of a transsyndesmotic reduction clamp on the anterior medial tibia resulted in the most accurate syndesmotic reduction and provided some protection against overcompression with large reduction clamp forces. Achilles tension appeared to contribute to reduction, decreasing the magnitude of measured malreduction from clamping. Clinical relevance: Previous studies estimating fibular malpositioning in cadaveric models that lacked passive muscle tension may have overestimated expected magnitudes of malalignment in patients treated with syndesmotic clamping. However, syndesmotic malreduction, particularly in the sagittal plane, was a real complication of syndesmotic clamping that was reduced by using an anterior position of the medial tine on the tibia.